Responsibilities of Notaries as a Public Official in Making Authentic Deeds - Wahid, Andi Ismayana; Mahka, Muh. Fachrur Razy; Sufriaman, Sufriaman (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
Notaries are given the authority to make general deeds, while PPAT (Land Deed Maker Official) is a general official who handles special deeds in the land sector. The deeds made by the two Notary and PPAT officials are authentic evidence which essentially contain formal truths that can be used by anyone in the future that a legal act as stated in the deeds has occurred. So that Notary and PPAT officials have a very important role in building certainty, order and legal protection in society. Therefore, the problem is the extent of a Notary's responsibility as a public official for the deed he makes and what sanctions can be given to the Notary if he violates the implementation provisions in making authentic deeds. To answer this problem, the method used is empirical juridical, namely research based on field research and equipped with library research. An authentic deed is perfect evidence which aims to guarantee certainty and legal protection to the parties. A notary must carry out his responsibilities properly in accordance with professional ethics (code of ethics) and in accordance with the Law on the Position of Notaries. This responsibility is not only based on morals but also based on law, especially Law Number 30 of 2004 concerning the Position of Notary Public in conjunction with Law Number 02 of 2014 concerning the Position of Notary Public.